Learning through visual displays - Schraw, Gregory J.; McCrudden, Matthew T.; Robinson, Daniel R. (Current perspectives on cognition, learning, and instruction., 2013)
The purpose of the volume is to explore the theory, development and use of visual displays and graphic organizers to improve instruction, learning and research. We anticipate five sections that address (1) frameworks for understanding different types of displays, (2) research-tested guidelines for constructing displays, (3) empirically-based instructional applications, (4) using displays to promote research and theory development, and (5) using displays to report test and research data to improve consumer understanding. Authors represent a variety of perspectives and areas of expertise, including instructional psychology, information technology, and research methodologies.The volume is divided into four sections. Section 1 provides a conceptual overview of previous research, as well as the contents of the current volume. Section 2 includes theoretical perspectives on the design and instructional uses of visual displays from major theorists in the field. These chapters discuss ways that visual displays enhance general cognition and information processing. Section 3 provides eight chapters that address the use of visual displays to enhance student learning. These chapters provide examples of how to organize content and use visual displays in a variety of ways in the real and virtual classroom. Section 4 includes three chapters that discuss ways that visual displays may enhance the research process, but especially improved data display.